2011
DOI: 10.1111/j.1365-2125.2010.03858.x
|View full text |Cite
|
Sign up to set email alerts
|

Daily administration of the TP receptor antagonist terutroban improved endothelial function in high‐cardiovascular‐risk patients with atherosclerosis

Abstract: CorrespondenceProfessor Serge Adnot, INSERM, Unité 955,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…The vascular remodeling, enhanced ROS and responsiveness to ET-1 and thromboxane in mice with RRM were prevented by genetic deletion of TP-Rs. Thus TP-R antagonists, which have already been used in clinical trials 21 , could be novel drugs to prevent vascular oxidative stress and CVD in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The vascular remodeling, enhanced ROS and responsiveness to ET-1 and thromboxane in mice with RRM were prevented by genetic deletion of TP-Rs. Thus TP-R antagonists, which have already been used in clinical trials 21 , could be novel drugs to prevent vascular oxidative stress and CVD in patients with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tested the hypothesis that ROS and ET-1generated in microvessels of mice with RRM depend on COX-2 generation of PGs and/or TxA 2 that activate TP-Rs. These studies have translational impact because drugs that block TP-Rs are already in clinical trials with promising responses 21 . If they were found to reduce vascular contractility, remodeling, ROS and ET-1 generation in CKD, they could fill a therapeutic void to prevent CVD which is now the principal cause of death and disability in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] In addition, Terutroban as a selective TPR antagonist, that is, a specific antagonist of the thromboxane A(2) and prostaglandin endoperoxide receptors, has shown to improve flow-mediated dilatation of the brachial artery after a single administration in patients with coronary artery disease. 15 Furthermore, coronary endothelial function has been shown to improve after Terutroban. 16 Several studies indicated that endothelial dysfunction and atherosclerosis are closely related.…”
Section: Discussionmentioning
confidence: 99%
“…In preliminary clinical trials with a limited number of subjects, terutroban has been demonstrated to improve endothelial function in CAD patients treated with aspirin, 82 or to improve endothelium-dependent vasodilatation and to inhibit platelet aggregation in high CV risk patients taking 300 mg of aspirin. 389 In addition, a very recent randomized, double-blind, placebo-controlled trial with 435 patients demonstrated that terutroban was at least as effective as aspirin in PAD patients 390 or even superior to it and similar to clopidogrel + aspirin for secondary prevention of ischemic stroke. 391 All in all, these data suggest TP receptor blockade to be at least as effective as aspirin in PAD and stroke, and to show synergism/potentiation with TXA 2 synthase inhibition in improving endothelial function in high-risk CV patients.…”
Section: Tp Receptor Antagonistsmentioning
confidence: 99%